Behavioral Sensitization to the Disinhibition Effect of Ethanol Requires the Dopamine/Ecdysone Receptor in Drosophila - Aranda, Gissel P.; Hinojos, Samantha J.; Sabandal, Paul R.; Evans, Peter D.; Han, Kyung-An (Frontiers in Systems Neuroscience, 2017)
Male flies under the influence of ethanol display disinhibited courtship, which is augmented with repeated ethanol exposures. We have previously shown that dopamine is important for this type of ethanol-induced behavioral sensitization but the underlying mechanism is unknown. Here we report that DopEcR, an insect G-protein coupled receptor that binds to dopamine and steroid hormone ecdysone, is a major receptor mediating courtship sensitization. Upon daily ethanol administration, dumb and damb mutant males defective in D1 (dDA1/DopR1) and D5 (DAMB/DopR2) dopamine receptors, respectively, showed normal courtship sensitization; however, the DopEcR-deficient der males exhibited greatly diminished sensitization. der mutant males nevertheless developed normal tolerance to the sedative effect of ethanol, indicating a selective function of DopEcR in chronic ethanol-associated behavioral plasticity. DopEcR plays a physiological role in behavioral sensitization since courtship sensitization in der males was reinstated when DopEcR expression was induced during adulthood but not during development. When examined for the DopEcR’s functional site, the der mutant’s sensitization phenotype was fully rescued by restored DopEcR expression in the mushroom body αβ and γ neurons. Consistently, we observed DopEcR immunoreactivity in the mushroom body calyx and lobes in the wild-type Canton-S brain, which was barely detectable in the der brain. Behavioral sensitization to the locomotor-stimulant effect has been serving as a model for ethanol abuse and addiction. This is the first report elucidating the mechanism underlying behavioral sensitization to another stimulant effect of ethanol.